2010
DOI: 10.1007/s00421-010-1421-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the weight training experience: a comparison of limb kinematics and EMG activity on three machines

Abstract: The aim of the study was to compare the kinematics and the timing and amount of electromyographic (EMG) activity during the lat-pull down exercise performed on machines that afforded one, two, or three degrees of freedom for the movement. Seven healthy men (age 29.4 +/- 5.6 years) participated in the study. The exercise was performed with a 30% 1-RM load. Three types of machines with varying degrees of freedom were used: Type 1, the conventional device that restricted the movement to a frontal plane; Type 2, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…These MVC trials are similar to those often reported in the literature for these muscles (e.g. Potvin, 1997;Ervilha et al, 2005;Koyama et al, 2010;Oliver et al, 2011).…”
Section: Experimental Protocolsupporting
confidence: 62%
“…These MVC trials are similar to those often reported in the literature for these muscles (e.g. Potvin, 1997;Ervilha et al, 2005;Koyama et al, 2010;Oliver et al, 2011).…”
Section: Experimental Protocolsupporting
confidence: 62%
“…Free weight exercises increases the stabilization requirements of the joint compared to stable machine exercises (Garhammer 1981;Koyama et al 2010;McCaw and Friday 1994). However, not all free weight exercises are the same.…”
Section: Introductionmentioning
confidence: 96%
“…To train their arm and finger capabilities, climbers usually perform pull-ups (Youdas et al, 2010). These exercises are also part of the usual training regimen for several other sports and previous analyses in the literature concerned non-climbers (Andersen, Fimland, Wiik, Skoglund, & Saeterbakken, 2014;Antinori, Felici, Figura, Marchetti, & Ricci, 1988;Koyama, Kobayashi, Suzuki, & Enoka, 2010;. One major difference between pull-ups for climbing objectives compared to fitness is the use of various types of grips, including gym bars, as well as large and small climbing holds.…”
Section: Introductionmentioning
confidence: 99%